Innovative food science and emerging technologies : the science behind health - Rajendran, Rajakumari; George, Anne, 1961-; Kalarikkal, Nandakumar; Thomas, Sabu (Apple Academic Press, 2019)
"Innovative Food Science and Emerging Technologies covers many new trends and developments in food science, including preparation, characterization, morphology, properties, recyclability, and advances and challenging opportunities. The volume considers food quality, shelf life, and manufacture in conjunction with human nutrition, diet, and health as well as the ever-growing demand for the supply and production of healthier foods. Distinguished scientists specializing in various disciplines discuss basic studies, applications, recent advances, difficulties, and breakthroughs in the field of food science and technology and also address topics of novel issues. The volume includes informative discussions and new research on food formulations, manufacturing techniques, biodegradably flexible packaging, packages foods, beverages, fruits and vegetable processing, fisheries, milk and milk products, frozen food and thermo processing, grain processing, meat and poultry processing, packaging, rheological characteristics of foods, heat exchangers in the food industry, food and health (including natural cures and food supplements), spice and spice processing, and more"--Resumé vydavatele
Keywords: potravinářství; potraviny; potravinářská technologie; inovace; biotechnologie; food industry and trade; food; food technology; innovations; biotechnology; sborníky; papers of several authors